Specific adaptations of neuromuscular control and knee joint stiffness following sensorimotor training - Gruber, M.; Bruhn, S.; Gollhofer, A. (International Journal of Sports Medicine, 2006)
The aim of this study was to examine how fixations of the ankle joint during sensorimotor training (SMT) influence adaptations in mechanical stiffness and neuromuscular control of the knee joint. Sixty-three healthy subjects were randomly assigned to three training groups that differed in their degree of ankle joint fixation, which was either barefooted, with an ankle brace or with a ski boot. Mechanical knee joint stiffness and reflex control of m. vastus medialis, m. vastus lateralis, m. biceps femoris, and m. semitendinosus were tested during force controlled anterior tibial displacements. This force was applied as both a fast and a slow stimulus. After the training period the group that trained barefooted showed an increase in mechanical stiffness of the knee joint from 79 ± 21 (Mean ± SD) N/mm to 110 ± 38 N/mm (p < 0.05) in the fast stimulus. The training group that trained with ski boots was able to improve knee joint stiffness from 67 ± 26 N/mm to 96 ± 47 N/mm (p < 0.05) in the slow stimulus. These improvements correspond with an enhanced activity of the hamstring muscles (m. biceps femoris and m. semitendinosus). From a more functional point of view, specific adaptations due to the fixation of the ankle joint may be helpful in the prevention and rehabilitation of knee joint injuries.